Objective-C for iPhone developers - Brannan, James A. (Emeryville, Calif. : McGraw-Hill, 2010)
"Shows you how to use the Objective-C programming language, Apple's Foundation framework, the iPhone SDK, and the Xcode development environment. ... Real-world examples throughout the book correspond with downloadable Ccode projects and video tutorials so you can get started with your first app right away."
Includes index
Recommends ready-to-use code that can be downloaded from www.mhprofessional.com/computingdownload and theauthor's website.
Keywords: Application software -- Development; Computer software -- Development; iPhone (Smartphone); Mobile computing; Objective-C (Computer program language)